Individual and community-level determinates of risky sexual behaviors among sexually active unmarried men: A multilevel analysis of 2016 Ethiopian Demographic and Health Survey. - Gedefaw Diress; Seteamlak Adane; Melese Linger; Abebe Merchaw; Belayneh Mengist (PLoS ONE, 2022)
Background In Ethiopia, HIV/AIDS continues to be a major public health problem mostly due to the high prevalence of risky sexual behaviors. However, research on risky sexual behavior and its determinants among unmarried men (never married, widowed, and divorced) who are highly vulnerable to risky sexual behavior was limited. Therefore, this study aimed to assess the magnitude of risky sexual behavior and its determinants among non-married men using a nationally representative sample. Methods The analysis was done on 5680 sexually active unmarried men aged 15-59 years using data from the 2016 Ethiopia Demographic Health Survey (EDHS). The main outcome variable was risky sexual behavior which defined as having at least one of the following: multiple sexual partners; initiation of sex before the age of 18 years; inconsistent condom use in the last 12 months; alcohol consumption at last sex. Multivariable generalized linear mixed-effects regression was employed to identify variables associated with risky sexual behavior. Result The overall magnitude of risky sexual behavior was 26.9% (95% CI; 25.7, 28.0). Currently employed (AOR = 2.49, 95% CI = 1.64-3.77), history of HIV testing (AOR = 2.51, 95% C = 1.95-3.23), drinking alcohol almost every day (AOR = 5.49, 95 CI = 2.73-11.02), and using Internet daily (AOR = 1.99, 95% CI = 1.06-3.74) increase the odds of risky sexual behavior. Whereas, primary education (AOR = 0.44, 95% CI = 0.32-0.61), secondary education level (AOR = 0.46, 95% CI = 0.29-0.72) and a high proportion of community-level media exposure (AOR = 0.42, 95% CI = 0.12-0.75) decrease the odds of risky sexual behavior. Conclusion In general, a significant proportion of sexually active unmarried men in Ethiopia have practiced risky sexual behavior. An intervention should be designed which are against the factors found to increase the odds of risky sexual behavior to reduce the incidence of HIV and other sexually transmitted infections.